Investigation of mechanical behaviour of natural composites (snake grass and elephant grass) with poly lactic acid - Thiruvasagam, C.; Prabagaran, S.; Suresh, P. (International Journal of Engineering and Technology, 2017)
The Poly Lactic Acid (PLA) is a completely biodegradable potential alternate of plastics applied in Civil infrastructural field because it posses very good â€œUltimate Withstandingâ€ properties. It can also be stated that hybrid fiber composite is having higher Mechanical and Physical characteristics compared with Mono fiber reinforced composite. Naturally existing Snake Grass (SG) and Elephant Grass (EG) reinforced PLA matrix fabrication is being narrated in this research article. By experimentation and analysis of results, it is proved that the Tensile strength, % Elongation, Flexural strength, Impact strength and Water absorption properties of SG & EG reinforced PLA composite is better than that of pure PLA Matrix.